HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN OTOT PUNGGUNG DENGAN HASIL LOMPAT TINGGI GAYA FLOP MAHASISWA KEPELATIHAN KELAS 2A TAHUN 2014/2015 - Nurwansyah, Siddiq; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is less the maximum capacity of high jump of flop style. The goal is to find out therelation of leg muscles explosive power andback muscles fleksibility with high jump results. The technique of sampling performed with total sampling of 32 students of Coaching Education of Riau University class 2A year 2014/2015. The type of this research is correlation. Normality of data used Lilliefors test, the product moment correlation test, with level of significance is α = 0.05, normalityof variabel X1, L0 (0,115) < Lt (0,157), normalityof variabel X2, L0 (0,117) < Lt (0,157), and the normality of variable Y, L0 (0,102) < Lt (0,157), so the distribution of the data is normal. The results of this research showed: there is a relation between explosive power of leg muscles andthe fleksibility of back muscles with high jump results, with rx1y correlation is 0,513 which is rhitung> rtabel or 0.672> 0,355, rx2ycorrelation is 0,449 which is 0,449 < 0,355, andR correlation is 0.672, which is 0,672 < 0,355.And such relations are categorized strong. Thus, Ho rejected and Ha accepted.Keyword: relation, exlosive power of leg muscels, fleksibility of back muscles,high jump results